2017
DOI: 10.1080/09585192.2017.1399431
|View full text |Cite
|
Sign up to set email alerts
|

Union partnership as a facilitator to HRM: improving implementation through oppositional engagement

Abstract: This paper provides a nuanced insight into the workplace level interactions between a union and HRM systems within a union-management partnership arrangement. Soft outcomes of HRM systems typically suffer from compromised implementation by managers struggling to balance competing operational priorities, but we show how a union limits this poor implementation. Qualitative and documentary data were retrieved from a major UK retailer and a trade union to examine how union activity interacts with HRM delivery.Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…improved productivity and enhanced quality of working life (Harley, 2020; Jo et al , 2020). Research indicates in a mutual gains environment, unionized workplaces can enhance the implementation and outcomes of the HPWS (see for example: Gill, 2009; Pyman et al , 2010; Gill and Meyer, 2013; Vernon and Brewster, 2013; MacKenzie et al , 2015; Cook et al , 2017). It follows that workplaces with a HPWS and a mutual gains ER arrangement may provide greater opportunities for employees to express organisation and employee-focused voice, as there will be pressure on the organisation to design voice mechanisms that facilitate both forms of voice.…”
Section: Integrated Model Of Employee Voice Systems and Behaviour Within Hpwsmentioning
confidence: 99%
“…improved productivity and enhanced quality of working life (Harley, 2020; Jo et al , 2020). Research indicates in a mutual gains environment, unionized workplaces can enhance the implementation and outcomes of the HPWS (see for example: Gill, 2009; Pyman et al , 2010; Gill and Meyer, 2013; Vernon and Brewster, 2013; MacKenzie et al , 2015; Cook et al , 2017). It follows that workplaces with a HPWS and a mutual gains ER arrangement may provide greater opportunities for employees to express organisation and employee-focused voice, as there will be pressure on the organisation to design voice mechanisms that facilitate both forms of voice.…”
Section: Integrated Model Of Employee Voice Systems and Behaviour Within Hpwsmentioning
confidence: 99%
“…While this process of oppositional engagement was seen as important to protect members' interests (Cook et al., 2020), there was a clear tension for the unions in that adopting a strongly confrontational approach might compromise the informal day‐to‐day relationships with managers, but failing to challenge managers risked alienating their own members. Indeed some union members felt JCCs only served to ‘rubber stamp’ decisions that had already been made by managers behind closed doors rather than offering a genuine opportunity for negotiation around alternative proposals:
How many times I've heard those words ‘it's a done deal [TU official, Local Council]
…”
Section: The Institutional Legitimacy Of Restructuringmentioning
confidence: 99%
“…In the UK, the 1992 Trade Union and Labour Relations (Consolidation) Act 1 sets out minimum consultation periods where there is a risk of redundancy (known as Section 188), the offer of alternative internal employment, and the entitlement to redundancy pay (roughly 1 week per year of service). However, since 2012 workers in the UK with less than 24 months continuous service are not entitled to statutory redundancy pay, and the low level of trade union membership density outside the public sector means that collective consultations typically relate to the timing rather than substantive content of restructuring proposals (Cook et al., 2020; McLachlan et al., 2020). However, following legal rules such as these may be the least that workers and trade unions expect.…”
Section: The Institutional Legitimacy Of Restructuringmentioning
confidence: 99%
“…Therefore, utilizing the power of other organizations may be an effective way to reconcile the dark side of HPWS and builds a fair and effective management system in the workplace (Guest, 2017 ). Trade unions are always regarded as facilitators to HRM through assistance and supervision in enterprises (Cook et al, 2020 ). For example, Chen et al ( 2018 ) found that union practice can create a harmonious labor-management atmosphere in the workplace, which improves the impression of the employees on the enterprise, thus strengthening the positive relationship between HPWS and the positive experience of employees.…”
Section: Introductionmentioning
confidence: 99%